Neurofibromin 1 Impairs Natural Killer T-Cell-Dependent Antitumor Immunity against a T-Cell Lymphoma - Liu, Jianyun; Gallo, Richard M.; Khan, Masood A.; Renukaradhya, Gourapura J.; Brutkiewicz, Randy R. (Frontiers in Immunology, 2018)
Neurofibromin 1 (NF1) is a tumor suppressor gene encoding a Ras GTPase that negatively regulates Ras signaling pathways. Mutations in NF1 are linked to neurofibromatosis type 1, juvenile myelomonocytic leukemia and Watson syndrome. In terms of antitumor immunity, CD1d-dependent natural killer T (NKT) cells play an important role in the innate antitumor immune response. Generally, Type-I NKT cells protect (and Type-II NKT cells impair) host antitumor immunity. We have previously shown that CD1d-mediated antigen presentation to NKT cells is regulated by cell signaling pathways. To study whether a haploinsufficiency in NF1 would affect CD1d-dependent activation of NKT cells, we analyzed the NKT-cell population as well as the functional expression of CD1d in Nf1+/− mice. Nf1+/− mice were found to have similar levels of NKT cells as wildtype (WT) littermates. Interestingly, however, reduced CD1d expression was observed in Nf1+/− mice compared with their WT littermates. When inoculated with a T-cell lymphoma in vivo, Nf1+/− mice survived longer than their WT littermates. Furthermore, blocking CD1d in vivo significantly enhanced antitumor activity in WT, but not in Nf1+/− mice. In contrast, a deficiency in Type-I NKT cells increased antitumor activity in Nf1+/− mice, but not in WT littermates. Therefore, these data suggest that normal NF1 expression impairs CD1d-mediated NKT-cell activation and antitumor activity against a T-cell lymphoma.